Tricks to publish in a high-impact journal - Zerfu, Taddese Alemu (2023)
Academic publishing in scientific, technical and medical (STM) journals entails disseminating information and the associated evidence-based interventions as a research paper in a relevant journal. Doing so often increases the visibility of one's research beyond one's immediate network of friends and colleagues. Publication in a high-impact journal, in particular, offers an opportunity for the researcher to disseminate original research questions, results and insights to a wider, frequently worldwide audience. More importantly, it can help the researcher advance their career by securing a new position, speaking opportunities at prestigious conferences or even by obtaining research funding. However, publishing in a high-impact journal is tough for many young researchers globally. A few of the tricks one can employ to publish in high-impact journals are further discussed below.